English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

the question is to Factor completely 9x^2-12x+4 or 9 x squared minus 12 X plus 4

2006-07-20 12:18:16 · 5 answers · asked by michael b 1 in Science & Mathematics Mathematics

5 answers

Try completing the square:
(ax + b)² + c = 0
a²x² + 2abx + b² + c = 0
a² = 9
a = +/-3
b² = 4
b = +/-2
2ab = -12
a = 3
b = -2
c = 0

So it's a square:
(3x-2)(3x-2)

Which can be rewritten as:
(3x-2)²

To find the roots, set this to zero:
(3x-2)² = 0

Which means:
3x-2 = 0
3x = 2
x = ⅔

2006-07-20 12:28:36 · answer #1 · answered by Puzzling 7 · 0 0

Multiply the outer terms and get 36
Find the factors of 36 that add up to be negative 12
-6 and -6
rewrite the problem as 9x^2-6x-6x +4
Tag the first two terms together and factor what they have in common and do the same for the second two terms
3x(3x-2) - 2(3x-2)
now factor out what these have in common which is
(3x-2) and you have (3x-2)(3x-2)

2006-07-20 22:07:04 · answer #2 · answered by msmath 1 · 0 0

So you've got a 9, a 12 and a 4.

Assuming whole numbers:
How many ways to get a 9 up front? 9x1 and 3x3.
How to get 4 in the back? 4 x 1 and 2 x 2.

Your answer will look like (ax-c)(bx-d) where x stays and the letters are numbers.

So try putting the options in the brackets, do the multiplication and see what works.

It wouldn't be fair to just give you the answer!
Edit:
Like the first two people did.

2006-07-20 19:32:21 · answer #3 · answered by n0witrytobeamused 6 · 0 0

The answer is (3X-2)^2. Since it's a negative 12x in the middle and a positive 4, that means both factors need to have a negative constant... Then you do the typical factoring and get your answer. :-)

2006-07-20 19:25:49 · answer #4 · answered by Chris 2 · 0 0

since 9x^2=(3x)^2 and 4 = 2^2 and 2*(3x)(2)=12x^2 we know this is a perfect square trinomial

(3x )(3x )
(3x 2)(3x 2)

now since middle is negative and end is positive we need 2 negative signs

(3x-2)(3x-2)


withn u=(3x-2) this is u^2 so we have (3x-2)(3x-2)=(3x-2)^2

get my 360 address IM me and i'll send u some tips

2006-07-20 21:33:47 · answer #5 · answered by ivblackward 5 · 0 0

fedest.com, questions and answers